Cyberbullying Exposure and Rejection Sensitivity as Predictors of Social Withdrawal - Kutsal, Ahmet; Maisarah, Syarifah; Viteri, Camila (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective: This study aimed to examine the predictive roles of cyberbullying exposure and rejection sensitivity in explaining social withdrawal among Malaysian adolescents. Methods and Materials: A correlational descriptive design was employed with a sample of 424 secondary school students in Malaysia, selected based on the Krejcie and Morgan sample size table. Participants completed standardized questionnaires assessing cyberbullying exposure (European Cyberbullying Intervention Project Questionnaire), rejection sensitivity (Rejection Sensitivity Questionnaire), and social withdrawal (Child Behavior Checklist subscale). Data were analyzed using SPSS version 27, with Pearson’s correlation tests used to examine the relationships among variables and standard multiple linear regression employed to identify the predictive power of the independent variables on social withdrawal. All assumptions of linearity, normality, homoscedasticity, and multicollinearity were verified prior to regression analysis. Findings: Pearson correlation results showed that social withdrawal was significantly and positively correlated with both cyberbullying exposure (r = .41, p < .01) and rejection sensitivity (r = .52, p < .01). The regression model was statistically significant, F(2, 421) = 109.72, p < .001, with an R² of .34, indicating that the model explained 34% of the variance in social withdrawal. Both predictors made significant contributions: cyberbullying exposure (B = 0.21, β = .28, t = 5.25, p < .001) and rejection sensitivity (B = 0.17, β = .41, t = 7.88, p < .001). Conclusion: These findings highlight the significant influence of both cyberbullying exposure and rejection sensitivity on adolescent social withdrawal. Rejection sensitivity emerged as a stronger predictor, suggesting that internal psychological dispositions may amplify the behavioral consequences of external stressors. Intervention programs targeting both online victimization and emotional-cognitive vulnerabilities are essential for mitigating social withdrawal in adolescents.